KONSEP MOTIVASI BELAJAR PERSPEKTIF AL-QURAN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Abdurrohim; Ali Mudlofir (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2024)
Currently, Indonesia ranks as the fourth most populous country globally, with 86% of the population being predominantly Muslim. Paradoxically, the literacy rate in Indonesia does not match its high population index. The latest report from the Program for International Student Assessment (PISA) survey revealed that Indonesia's literacy rate ranked 62nd out of 70 countries in 2019. Meanwhile, Islamic education faces the challenge of nurturing a generation capable of critical thinking for their livelihoods. On the other hand, literacy is highly encouraged in Islam, as stated in the Quran. The initial verses of the holy book, such as Al-'Alaq: 1-5, encourage humans to learn and read. However, literacy in the context of Islamic education is often perceived merely as physical skill training, without understanding the essence and purpose of the process. Therefore, the aim of this research is to delve deeper into the concept of learning motivation in the Quran, specifically related to the verses discussing it, using Library Research methods and employing thematic and semantic analysis approaches. The research identifies two varieties of Quranic strategies: Intrinsic and Extrinsic, each with different patterns and motifs. These strategies encompass directives and prohibitions, inspirational stories, titles and self-actualization, as well as rewards and punishments. All of these aspects are interconnected with motivating individuals to engage in learning activities, spanning visual, oral, listening, writing, drawing, and mental activities. This concept is crucial for family environments, school settings, and study groups.